2019
DOI: 10.3904/kjim.2018.187
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cough, not asthma, is associated with depression in the elderly: a community-based population analysis in South Korea

Abstract: Background/AimsDepression and allergic diseases, including asthma, are frequently reported as comorbid conditions. However, their associations have been rarely examined in community-based elderly populations.MethodsThe analyses were performed using the baseline data set of the Korean Longitudinal Study of Health and Aging, which consists of 1,000 elderly participants (aged > 65 years) randomly recruited from an urban community. Depression was assessed using the Geriatric Depression Scale, Center for Epidemiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…A South Korean study similarly found a significant association Open access between chronic, frequent and nocturnal cough and depression. 12 Disturbed sleep, anxiety and depression were also commonly reported among patients with CC in a UK study, in respectively 70%, 69% and 55% of patients with CC. 32 In this study, currently employed patients with CC reported a significantly higher impairment of work productivity compared with matched non-cough respondents.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A South Korean study similarly found a significant association Open access between chronic, frequent and nocturnal cough and depression. 12 Disturbed sleep, anxiety and depression were also commonly reported among patients with CC in a UK study, in respectively 70%, 69% and 55% of patients with CC. 32 In this study, currently employed patients with CC reported a significantly higher impairment of work productivity compared with matched non-cough respondents.…”
Section: Discussionmentioning
confidence: 92%
“…11 CC has also been associated with increased rates of depression. 12 In Japan, one study revealed that patients with CC with cough variant asthma had impaired QoL as measured by the Leicester…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, chronic cough is frequently comorbid with respiratory and non-respiratory diseases, 27 35 making the cough-related QoL data difficult to interpret, although we think that comorbidity is part of a disease, either in terms of the pathophysiology or causal relationships. Depression is frequently associated with chronic cough 12 28 36 37 ; however, depression in patients with chronic cough is likely to be a consequence of cough, because it significantly improves with cough resolution. 28 However, depression is considered as a major confounder in the present study, because it is a part of EQ-5D dimension score and also its implication may be different from that in specialist cough clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic cough and symptoms of depression are reported to be closely related, and improvement of cough was correlated with improvement in depression scores. 1 11 12 Depression comorbidity is important for the QoL; thus, the impact of chronic cough on the QoL should be assessed after completely excluding the effects of depression. However, it is very difficult to achieve this in reality.…”
mentioning
confidence: 99%